Use of a mobile health application in wellness : an assessment of needs, perceptions, usability and efficacy in changing dietary choices in a university student population - Slazus, Cecil (Stellenbosch : Stellenbosch University, 2019)
Thesis (MNutr)--Stellenbosch University, 2019.